PHYTOCHEMICAL PROFILING AND GC-MS ANALYSIS OF AQUEOUS METHANOL FRACTION OF SEVYACHANDANADI LEPA - Dhanashri S. Dhavale
The skin, a critical barrier and a complex organ, is vulnerable to toxins, causing disorders like contact dermatitis. Ayurveda highlights application of formulations such as Sevyachandanadi lepa, derived from the Astanga Hridaya Sutrasthana, for managing Sparshaja Visha (contact poisoning). This study explored the therapeutic potential of Sevyachandanadi lepa, prepared using eight drugs and analyzed through physicochemical, phytochemical, GC-MS and UV-spectroscopy methods. The Lepa demonstrated low moisture content, stability and the presence of active compounds like flavonoids, tannins and alkaloids, with potent anti-inflammatory, antioxidant and antimicrobial properties. GC-MS revealed 13 bioactive constituents, including alpha-Santalol (37.04%), Dehydrocostus lactone (23.76%), and beta-Santalol (11.86%), supporting its efficacy. The findings scientifically validate Sevyachandanadi lepa as a safe, holistic remedy for inflammatory skin disorders and microbial infections, aligning with traditional ayurvedic applications. Further research may enhance its integration into dermatological therapeutics.